Parenting Education for Early Childhood Social-Emotional Development - Agus Suprijanto; Etty Kartikawati; May Roni; Sri Purwanti N (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
Social-emotional development is a process that includes changes in individuals with other people, changes in emotions, and personality changes. One of the potentials and abilities of children that need to be developed by educators and parents is the potential social-emotional abilities of children. Harmonious interaction will facilitate the child's socialization process. So the family is the most critical institution in child development. This research uses case study research with descriptive qualitative research methods involving teachers, parents, and children, Data was collected through observation, interviews, and documentation. This research was conducted at Qurrota A'yun Kindergarten, East Betung Bay. The sample was shown to parents who have early childhood and attend Qurrota A'yun Kindergarten in East Betung Bay. Then the data that has been collected is analyzed and presented in narrative form so that the desired conclusions can be drawn. The results showed that the role of family education in children's social-emotional development at Qurrota A'yun Kindergarten in Teluk Betung Timur plays a good role. This is due to the exemplary education carried out by parents/family in words, deeds, attitudes, and behavior that can help children know feelings of pleasure, sadness, anger and fear. Optimally in teaching to get along or socialize with others helps children make friends, play and work together with others.